1981
DOI: 10.1111/j.1365-3032.1981.tb00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidance of flying male moths by wind‐borne sex pheromone

Abstract: ABSTRACT. On passing from clean air into a homogeneous cloud of sex pheromone in a wind tunnel flying male Adoxophyes orana (F.v.R.) (Lepidoptera: Tortricidae) turned more or less upwind and reduced the time and distance between their switchings of track from one side of the wind line to the other. These responses became adapted under the constant pheromone stimulation in the cloud, thereby arresting upwind progress; but the adapted moths would now ‘lock‐on’ to an added pheromone plume and advance upwind alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0
2

Year Published

1991
1991
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(117 citation statements)
references
References 31 publications
3
112
0
2
Order By: Relevance
“…Temporal characteristics of ORN responses to odours are another feature of odour coding, which is especially important to enable odour discrimination while flying or walking upwind (Baker 1985, Kennedy et al 1981, Kramer 1992. A response is called phasic if the frequency of firing action potentials decreases abruptly shortly after the onset of the excitation response.…”
Section: Figure 3 Schematic Diagrams Of Single-and Double-wall Structmentioning
confidence: 99%
See 2 more Smart Citations
“…Temporal characteristics of ORN responses to odours are another feature of odour coding, which is especially important to enable odour discrimination while flying or walking upwind (Baker 1985, Kennedy et al 1981, Kramer 1992. A response is called phasic if the frequency of firing action potentials decreases abruptly shortly after the onset of the excitation response.…”
Section: Figure 3 Schematic Diagrams Of Single-and Double-wall Structmentioning
confidence: 99%
“…An intermittent frequency of odour stimulus is often essential in order to elicit a behavioural response (Baker et al 1985, Kennedy et al 1981. For example, a homogeneous plume of CO 2 is sufficient to activate upwind flight behaviours in Ae.…”
Section: Temporal Coding and Stimulus Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with the tortricids Adoxophyes orana (Kennedy et al, 1981) and Grapholita molesta (Willis and Baker, 1984;Baker et al, 1985) in homogeneous pheromone clouds revealed that fluctuating pheromone stimulation was required for upwind flight. However, the males of the pyralid C. cautella fly upwind both in homogeneous clouds of pheromone (Justus and Carde, 2002) and along pheromone plumes pulsed at rates as high as 25 Hz (Justus et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of this periodic stimulation has been experimentally studied and shown to be a necessary condition of odorant perception, because the moth cannot orient in an artificially made uniform cloud. Behavioural (Kennedy et al, 1980(Kennedy et al, , 1981Vickers and Baker, 1992;Willis and Baker, 1984) and neurophysiological (Christensen and Hildebrand, 1988;Marion-Poll and Tobin, 1992;Rumbo and Kaissling, 1989) experiments indicate that the optimum frequency is in the range 1Á/10 Hz. Our aim in the present paper is to investigate to what extent this optimum frequency can be explained by the characteristics of the peripheral sense organs.…”
Section: Introductionmentioning
confidence: 96%